Environmental factors related to differences in the microbiota in the upper respiratory tract in young children: Focusing on the impact of early nursery attendance - Abushawish, Asmaa; Haro, Kaoru; Hoshina, Takayuki; Kitajima, Naoko; Kusuhara, Koichi (Frontiers in Pediatrics, 2023)
Background: Microbial colonization of the upper respiratory tract (URT) during the first years of life differs significantly according to environmental factors. We investigated the association between early nursery attendance, URT infection (URTI) and drugs used for its treatment and the differences in the URT microbiota. Methods: This prospective study included 33 young children (11 and 22 with and without nursery attendance during their infancy, respectively). URT secretions were collected from the nasopharynx of these children at 2, 4, 6, 12, 18 and 24 months old. Clinical information after the latest sampling, including histories of URTI and the uses of antibiotics or cold medicines, was collected from all children. URT bacteria were identified by a clone library analysis of the 16S rRNA gene. Results: In the diversity of URT microbiota using the Shannon index, we did not detect any associations between variations in the URT microbiota and environmental factors (nursery attendance, development of URTIs, or the uses of antibiotics or cold medicines). However, in a clustering analysis, the proportion of the samples classified as Corynebacterium propinquum-dominant cluster was significantly lower in children ≥6 months old with nursery attendance than in those without nursery attendance. In addition, the URT microbiota was significantly different between samples from children ≥6 months old with and without a history of ≥3 URTI episodes after the first sampling. Furthermore, the URT microbiota was also significantly different between samples from these children with and without antibiotic use between the previous and present samplings. Conclusion: Early nursery attendance and its related factors, including the frequency of URTI and antibiotic treatment, may be associated with the differences in the URT flora in young children.